LUT based aerosol size distribution determination from wavelet de-noised LiDAR data - Dela Cruz, Mannelyn J. (Animo Repository, 2004)
Eleven Aerosol Size Distributions (ASD) (from Urban to Maritime with 9 logarithmic increments in between them) was simulated in this study to generate a Lookup Table (LUT). In the simulations, aerosol size ranged from 0.001-10Î¼m with 1.40 to 1.60 real and 0.000-0.030 imaginary refractive indices for 355-, 532-, 368- and 862-nm wavelengths. The 355- and 532-nm wavelengths are used in the LiDAR while the 368- and 862-nm wavelengths are for the SunPhotometer. The Signal-to-Noise Ratio (SNR) and correlation coefficient squared were computed for the LiDAR signal at 355- and 532- nm denoised using the Haar, Daubechies, Coifman, Symlet, and Beylkin wavelet bases. After testing 2,715 files, it was seen that the Haar wavelet was the best wavelet in denoising the LiDAR signal since it gave the highest SNR and correlation coefficient squared. The extinction coefficients calculated using Fernalds inversion method used LiDAR data denoised using the Haar wavelet. The ASD in the De La Salle University area was determined by comparing the ratio of extinction coefficients to values found in the LUT. The ASD of the data analyzed falls on the two extreme ASD models considered. Results have also shown that the ASD, and consequently the type of aerosols interacting with the LiDAR, is affected by the local meteorological conditions and mans activities (e.g., fireworks during New Years eve).